Ethics in Psychology and Education research in Portugal: contributions to think about the Brazilian case (Práxis Educativa, 2020)
This article presents a study on the Portuguese model of conduct regulation in research in the areas of Education and Psychology in order to contribute to the Brazilian debate on this topic. Regarding the method, it is an exploratory research with a quantitative and qualitative approach, based on documentary analysis combined with the objective hermeneutic analysis of data collected through the survey technique, used to survey the opinions of doctoral students in Education and in Psychology from Portugal. It is possible to point out as the main conclusions of the study: (1) the similarity between the two models regarding a mostly normative confrontation of the ethical question in research; and (2) the more decentralized character of the Portuguese model, which combines general transnational guidelines with normative sectoral and national ones, with greater participation of Universities, associations representing different areas and researchers themselves.Keywords: Ethics in research. Regulation. Psychology and Education. Portugal and Brazil.